Strategies for Using and Utilizing Zakat Funds in an Effort to Maintain Family Resilience in The Midst of the Covid-19 Pandemic from the Perspective of Maq??hid Asy- Syar?'ah - Eryanti (Journal of Law and Social Politics, 2023)
In the development of the times, the problems that occur are increasing, including the spread of the COVID-19 pandemic in Indonesia which hurts human life, such as the impact on the economic sector which increases the number of poverty rates that occur in society. In this case, both the government and community social institutions are trying to carry out various strategies to help restore the order of human life affected by the COVID-19 pandemic. One of the social institutions that participate in helping this problem is the Amil Zakat Institute (LAZ) Thoriqotul Jannah Center Cirebon, it is not yet known how the LAZ Center's strategy is to assist the government in solving the COVID-19 disaster management, therefore this is very important. It is interesting to point out the strategy carried out by the LAZ Center to assist the government in solving the COVID-19 disaster management through direct field research. This study aims to determine how the strategy for the use and utilization of zakat funds to maintain family resilience in the covid-19 pandemic from the perspective of Maq??id Asy-Syar?'ah. This study uses qualitative research methods, data obtained by conducting observations, interviews (interviews), documentation which is then analyzed using descriptive analysis methods. The results of this study are first, the strategy carried out by the LAZ Center in using consumptive zakat funds is applied in economic programs such as food package assistance, incidental social assistance given to the poor, elderly, and converts as well as tuition assistance (scholarships) given to the poor. orphans and poor people. The two strategies for utilizing funds carried out by the LAZ Center are by providing business capital assistance to traders who are victims of the COVID-19 pandemic and providing guidance and assistance to fostered partners. The three strategies for the use and utilization of zakat funds carried out by the LAZ Center are by the five elements in the objectives of sharia (Maq??id Asy-Syar?'ah) namely maintaining religion, soul, mind, lineage, and property.